2017
DOI: 10.3892/etm.2017.4704
|View full text |Cite
|
Sign up to set email alerts
|

Roles of p38 and JNK protein kinase pathways activated by compound cantharidin capsules containing serum on proliferation inhibition and apoptosis of human gastric cancer cell line

Abstract: Abstract. The aim of the present study was to investigate the inhibitory effect of compound cantharides capsules (CCCs) on the viability and apoptosis of human gastric cancer cell lines, BGC-823 and SGC-7901, and to detect its regulation of gene expression levels, as well as its inhibition mechanisms. Each cell line was grouped into a control group, CCC serum group, 5-fluorouracil (5-FU) group, combination therapy group (CCC serum + 5-FU) and serum control group. Growth curves were measured and flow cytometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The results showed that GRP78 protein expression was activated at low concentrations of CTD (6.25 μM) and inhibited at higher concentrations, ie, 12.5, 25, and 50 μM CTD. GRP78 is the main regulator of UPR; under stress, it dissociates from PERK and PERK forms oligomers and is activated by self‐phosphorylation (Chen, Melchior, & Guo, 2015; Sun, Zhang, Mao, Lu, & Jiao, 2017). Activated PERK can specifically phosphorylate the serine 51 of eIF2α (Zhi, Huan, Sun, & Chao, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that GRP78 protein expression was activated at low concentrations of CTD (6.25 μM) and inhibited at higher concentrations, ie, 12.5, 25, and 50 μM CTD. GRP78 is the main regulator of UPR; under stress, it dissociates from PERK and PERK forms oligomers and is activated by self‐phosphorylation (Chen, Melchior, & Guo, 2015; Sun, Zhang, Mao, Lu, & Jiao, 2017). Activated PERK can specifically phosphorylate the serine 51 of eIF2α (Zhi, Huan, Sun, & Chao, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the H 2 O 2 production, after 20 minutes of constant irradiation and a potential kept at 0 V vs. Ag/AgCl, an aliquot was taken from the electrolyte solution and analyzed. A fluorimetric test based on horseradish peroxidase [37,38] was used to quantify the concentration of produced H 2 O 2 , based on a calibration curve (Supporting Information, Figure S9). The results show that S-2/TiO 2 devices exhibit an average production of H 2 O 2 that is 37 % lower than that of a-2/ TiO 2 (Table 1).…”
Section: Device Testingmentioning
confidence: 99%
“…2 ) is a sesquiterpenoid bioactive substance extracted from the blister beetle of the genus Mylabris , which has been applied for more than 2000 years in traditional Chinese medicine 26 , 27 . Studies have reported the cytotoxic effects of cantharidin on several cancers, such as hepatocellular 28 , 29 , gastric 30 , 31 , breast 32 , 33 and colorectal cancers 34 , 35 . However, the miR-214-3p/DKK3/GSK-3β/β-catenin/LEF1 axis related pharmacological mechanism of cantharidin on osteosarcoma remains unknown.…”
Section: Introductionmentioning
confidence: 99%